Health information seeking behaviour: a concept analysis - Zimmerman, Margaret S.; Shaw, George (Health information and libraries journal, 2020)
Background In 2007, Lambert and Loiselle conducted an extensive concept analysis of the term health information seeking behaviour (HISB) to examine the concept's level of maturity and critically analyse its characteristics. Since their groundbreaking work, HISB has evolved with the proliferation of ICTs. The Internet is now a common and often preferred medium for the pursuit of health information. Objectives The previous analysis spanned 42 years of literature; this article describes an analysis of the last 10 years of literature on HISB and how online seeking has caused the concept to evolve in the literature. Methods This study used the concept analysis methodology employed by Lambert and Loiselle in the original analysis. It also included a systematic search conducted in five databases to identify studies from 2007 to 2017, using similar inclusion criteria from the original study. Results Of the more than 500 articles retrieved, 85 journal articles met the inclusion criteria. Consistent with the original work, articles that included outcomes were identified as either behavioural or cognitive. Conclusion Most of the attention of the works studied focused on individuals and their information source preferences. This HISB analysis can be incorporated with studies to understand how various communities seek information in online versus non‐online contexts.